Prevalence of hepatopathy in type 1 diabetic children - Al-Hussaini Abdulrahman A; Sulaiman Nimer M; AlZahrani Musa D; Alenizi Ahmed S; Khan Mannan (BMC, 2012)
Abstract Background The Prevalence of liver disease among diabetics has been estimated to be between 17% and 100%. Most of these data were obtained from adult studies. The aim of our study was to screen for liver disease among type 1 diabetic children. Methods Children with type 1 diabetes following in clinic have been examined for existence of liver disease, from November 2008 to November 2009. All were subjected to the following: History, physical examination, liver function tests, fasting lipid profile, HbA1C, and ultrasound of the liver. A hyperechogenic liver and/or hepatomegaly on ultrasound were attributed most likely to excess glycogen or fat in the liver, after negative extensive work-up to rule out other underlying liver disease. Results 106 children with type 1 diabetes were studied: age ranged between 8 months to 15.5 years, sixty two patients were females. Twenty two patients (21%) were identified to have abnormal findings on ultrasound of the liver: 10 patients had hepatomegaly and 12 had hyperechogenic liver. The group with hyperechogenic liver had poorer glycemic control than patients with normal liver (Mean HbA1c 12.14% Vs 10.7%; P value = 0.09). Hyperechogenic liver resolved in 60% at 6 months follow-up upon achieving better glycemic control. Conclusions Hyperechogenic liver and/or hepatomegaly are not uncommon in children with type 1 diabetes and tend to be more prevalent among children with poor glycemic control. Type 1 diabetes related hepatopathy is reversible by optimizing glycemic control. Because of its safety, and reliability, ultrasound can be used to screen for hepatopathy in type 1 diabetic child.